2021
DOI: 10.1080/07391102.2021.1914168
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of the hepatitis C drugs and amentoflavone could interfere with binding of the spike glycoprotein of SARS-CoV-2 to ACE2: the results of a molecular simulation study

Abstract: The worldwide rapid spread of the COVID-19 disease necessitates the search for fast and effective treatments. The repurposing of existing drugs seems to be the best solution in this situation. In this study, the molecular docking method was used to test 248 drugs against the receptor-binding domain (RBD) of spike glycoprotein of SARS-CoV-2, which is responsible for viral entry into the host cell. Among the top-ranked ligands are drugs that are used for hepatitis C virus (HCV) treatments (paritaprevir, ledipasv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 101 publications
0
4
0
1
Order By: Relevance
“…There are also four docking studies targeting spike glycoprotein RBD of SARS-CoV-2. These studies reveal that AMF can strong bind with spike glycoprotein RBD of SARS-CoV-2 with the binding energies: -7.6 kcal/mol ( Wei et al, 2020 ), -8.7 kcal/mol ( Puttaswamy et al, 2020 ), -8.5 kcal/mol ( Miroshnychenko and Shestopalova (2021) ) and -10.2 kcal/mol ( Rameshkumar et al, 2021 ). However, the binding sites of AMF are different in these studies.…”
Section: Anti-sars-cov-2 Effect Of Amentoflavonementioning
confidence: 85%
See 1 more Smart Citation
“…There are also four docking studies targeting spike glycoprotein RBD of SARS-CoV-2. These studies reveal that AMF can strong bind with spike glycoprotein RBD of SARS-CoV-2 with the binding energies: -7.6 kcal/mol ( Wei et al, 2020 ), -8.7 kcal/mol ( Puttaswamy et al, 2020 ), -8.5 kcal/mol ( Miroshnychenko and Shestopalova (2021) ) and -10.2 kcal/mol ( Rameshkumar et al, 2021 ). However, the binding sites of AMF are different in these studies.…”
Section: Anti-sars-cov-2 Effect Of Amentoflavonementioning
confidence: 85%
“…However, the binding sites of AMF are different in these studies. Wei et al (2020) and Rameshkumar et al (2021) suggest that AMF binds with the outside of the ACE2-binding region, while Miroshnychenko and Shestopalova, (2021) . and Puttaswamy et al (2020) reveal that AMF binds with the ACE2-binding region.…”
Section: Anti-sars-cov-2 Effect Of Amentoflavonementioning
confidence: 99%
“…In a study of screening FDA-approved drugs, iron oxide nanoparticles were suggested for COVID-19 treatment . Existing drugs, such as amentoflavone, ledipasvir, tenofovir, levodopa, lopinavir, and ubrogepant, against S protein were investigated. For natural products inhibiting S protein, studies focusing on indigenous food additives, herbal constituents, antioxidants, traditional medicinal plants, tea, and others suggested potent inhibitors such as phycocyanobilin, phycoerythrobilin, phycourobilin, folic acid, hinokiflavone, and phytochemicals. Lastly, some other compounds are repurposed to inhibit the S protein.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…This has been supported by molecular dynamic docking studies [ 18 , 19 ]. Amentoflavone has also been reported to bind to the receptor binding site of the spike glycoprotein of SARS-CoV-2 with a binding energy of −8.5 kcal/mol [ 20 ].…”
Section: Amentoflavone As An Antiviral Agentmentioning
confidence: 99%